Linguistic peculiarities of hybrid nominations in the modern Kazakh language - Nessipbay А.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Language as a means of human communication and means of thinking, is going through its own historical path, but at the same time an important fact is that it is formed and enriched owing to other foreign languages. Aims and objectives of research: to consider the linguistic nature of hybrid nominations in the modern Kazakh language, to give a general idea about them, to identify reasons, ways of emergence of hybrid nominations in language, to identify features and patterns of their occurrence. In connection with this goal, the following tasks are performed definition of models of hybrid nominations in the modern Kazakh language, to make a substantiation of structural and semantic characteristics of hybrid names, taking into account the morphological structure and features of implementation of wordformation models and development of a classification of hybrid nominations in the Kazakh language. Currently, hybrid words are widely used in our native language, especially after our country gained its independence, the number and usage of hybrid words in language has increased dramatically. Thus, it is very important to identify linguistic and extralinguistic reasons and factors for sharp increase in number of hybrid terms in language, the ways of their formation, as well as semantic, structural features. Practical significance of research: theoretical conclusions and results of the research will serve as the basis for further scientific research on this issue; the materials of work can serve as a methodological aid, as well as in preparation of a dictionary of hybrid words.